Sosialisasi Pelestarian Bahasa Daerah dengan Pengaplikasian Bangga Berbahasa Daerah - Nasrun, Siti Hajar Putri Maharani; Husain, Firman (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2025)
Community Service Program (KKN) is a form of student service to the community aimed at applying knowledge in real life. One of the commonly conducted work programs in KKN is school socialization, which aims to enhance students' understanding of important issues. This socialization program covers the fields of Education and Culture. The methods used in the socialization process include counseling, interactive discussions, and conducting assessments. The results of this activity show that structured and student-participatory socialization can increase awareness and encourage positive behavioral changes. Thus, the socialization work program at KKN has a significant impact on student empowerment and strengthens the role of students as agents of social change.